Transmission of hemagglutinin D222G mutant strain of pandemic (H1N1) 2009 virus. - Puzelli, Simona; Facchini, Marzia; Spagnolo, Domenico; De Marco, Maria A; Calzoletti, Laura; Zanetti, Alessandro; Fumagalli, Roberto; Tanzi, Maria L; Cassone, Antonio; Rezza, Giovanni; Donatelli, Isabella (Emerg Infect Dis, 2010)
A pandemic (H1N1) 2009 virus strain carrying the D222G mutation was identified in a severely ill man and was transmitted to a household contact. Only mild illness developed in the contact, despite his obesity and diabetes. The isolated virus reacted fully with an antiserum against the pandemic vaccine strain.
Keywords: Adult; Amino Acid Substitution; Disease Outbreaks; Hemagglutinin Glycoproteins, Influenza Virus; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Middle Aged; Mutation, Missense; Phylogeny; Retrospective Studies; RNA, Viral; Sequence Analysis, RNA; Severity of Illness Index